Development and Preliminary Application of Multiplex Loop-Mediated Isothermal Amplification Coupled With Lateral Flow Biosensor for Detection of Mycobacterium tuberculosis Complex - Wang, Xingyun; Wang, Guirong; Wang, Yacui; Quan, Shuting; Qi, Hui; Sun, Lin; Shen, Chen; Huang, Hairong; Jiao, Weiwei; Shen, Adong (Frontiers in Cellular and Infection Microbiology, 2021)
The aim of this study was to develop a simple and reliable method to detect Mycobacterium tuberculosis complex (MTBC) and verify its clinical application preliminarily. A loop-mediated isothermal amplification method coupled with lateral flow biosensor (LAMP-LFB) assay, was developed and evaluated for detection of MTBC. Two sets of primers, which targeted IS6110 and IS1081 sequences of MTBC, were designed for establishment of multiplex LAMP-LFB assay. The amplicons were labelled with biotin and fluorescein isothiocyanate (FITC) by adding FITC labelled primer and biotin-14-dATP and biotin-14-dCTP and could be visualized using LFB. The optimal reaction conditions of multiplex LAMP-LFB assay confirmed were 66°C for 50 min. The analytical sensitivity of multiplex LAMP-LFB is 10 fg of genomic templates using pure culture, and no cross-reactivity with other common bacteria and non-tuberculous mycobacteria strains was obtained. A total of 143 clinical samples collected from 100 TB patients (62 definite TB cases and 38 probable TB cases) and 43 non-TB patients were used for evaluating the feasibility of multiplex LAMP-LFB assay. The multiplex LAMP-LFB (82.0%, 82/100) showed higher sensitivity than culture (47.0%, 47/100, P < 0.001) and Xpert MTB/RIF (54.0%, 54/100, P < 0.001). Importantly, the multiplex LAMP-LFB assay detected additional 28 probable TB cases, which increased the percentage of definite TB cases from 62.0% (62/100) to 90.0% (90/100). The specificity of multiplex LAMP-LFB assay in patients without TB was 97.7% (42/43). Therefore, multiplex LAMP-LFB assay is a simple, reliable, and sensitive method for MTBC detection, especially in probable TB cases and resource limited settings.